The Effect of Recycled Material and Buton Granular Asphalt (BGA) on Asphalt Concrete Mixture Performance - Novita Pradani; Rita Irmawaty; Muhammad W. Tjaronge; Irwan R. Rahim (Salehan Institute of Higher Education, 2023)
Pavement recycling is an appropriate technology for constructing and restoring road pavement structures due to the limited supply and high cost of pavement materials. This study aims to improve the recycled mix's performance by replacing the fine aggregate in the recycled mix for road pavement with Buton Granular Asphalt (BGA). The percentage of recycled material (Reclaimed Asphalt Pavement/RAP) in the mixture was limited to 20% and 30% by weight of the total mixture. BGA was added by 3%, 6%, and 9% in each mixture with the RAP variation. Mixture performance was obtained through Indirect Tensile Strength (ITS) testing. The ITS test results showed that the ITS value of the mixture with RAP and BGA increased by an average of 4.7–15% compared to the mixture without RAP and BGA. The Toughness Index (TI) value increased by 3.5–19.8% with the addition of RAP. With the addition of 3% BGA, the TI value tends to increase and subsequently decrease up to 9% BGA levels. The result indicated that adding 30% RAP and 3% BGA to the mixtures improved pavement performance and could be a solution to increase the elasticity and fracture resistance of the mixture. Doi: 10.28991/CEJ-2023-09-06-09 Full Text: PDF